Biochemical and physiological modifications in tissues of Sardina pilchardus: spatial and temporal patterns as a baseline for biomonitoring studies - Nunes, Bruno S.; Travasso, Rita; Gonçalves, Fernando; Castro, Bruno B. (Frontiers in Environmental Science, 2015)
Sardina pilchardus is a marine species common in the North Atlantic Ocean, and is subjected to diffuse anthropogenic chemical contamination and seasonal fluctuations in biotic and abiotic parameters that may alter its physiology and condition. Biological material is easily available through commercial fisheries, which could facilitate its use as a bioindicator species. The aim of the present work was to address its potential inclusion in biomonitoring studies, considering a combinatory approach through the use of enzymatic biomarkers and somatic indices, by assessing spatial and temporal patterns in a metapopulation along the west coast of Portugal. Our results showed significant variability of the biochemical and physiological profile of the fish, mainly concordant between sampling sites. Large differences for most markers were found across periods of the year, showing the importance of seasonality, which was mostly related to the reproductive cycle. Hence, environmental scientists should acknowledge seasonality as a strong driving force for physiological adaptations, influencing biochemical markers that are normally used to identify effects of chemical contamination. The here-obtained set of data suggests that S. pilchardus may be successfully included in oceanic biomonitoring studies, when one considers that the contribution of seasonal factors may exceed the influence of eventual anthropogenic contamination.